2014
DOI: 10.4137/cin.s12419
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Microscopy Signal Processing Strategies in Cancer

Abstract: This work reviews the most relevant present-day processing methods used to improve the accuracy of multimodal nonlinear images in the detection of epithelial cancer and the supporting stroma. Special emphasis has been placed on methods of non linear optical (NLO) microscopy image processing such as: second harmonic to autofluorescence ageing index of dermis (SAAID), tumor-associated collagen signatures (TACS), fast Fourier transform (FFT) analysis, and gray level co-occurrence matrix (GLCM)-based methods. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 55 publications
1
42
0
7
Order By: Relevance
“…This reflects the fact that there is a link between epithelial carcinogenesis process and progressive loss in the fine fibril structure. These results are in accordance with previous studies in which the correlation analysis was applied to the stroma of human biopsies from both different epithelial tumors and breast adenocarcinoma . For instance, these studies have demonstrated that collagen fibers were irregularly distributed without a well‐defined orientation in pathological samples, while the morphology of the collagen fibers were highly arranged in normal samples.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This reflects the fact that there is a link between epithelial carcinogenesis process and progressive loss in the fine fibril structure. These results are in accordance with previous studies in which the correlation analysis was applied to the stroma of human biopsies from both different epithelial tumors and breast adenocarcinoma . For instance, these studies have demonstrated that collagen fibers were irregularly distributed without a well‐defined orientation in pathological samples, while the morphology of the collagen fibers were highly arranged in normal samples.…”
Section: Resultssupporting
confidence: 92%
“…How collagen architecture changes during pathologic status is currently used as a clinical biomarker for tumor diagnosis and staging . For example, SHG and third harmonic generation imaging have been used to monitor tumor progression and carcinogenesis . Information about the interactions between tumor cells, extracellular matrix, and epithelial‐stromal communication, as well as the initiation of collagen remodeling, can be obtained .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The index indicates the fibrotic status of the dermis. The SAAID decreases with photoaging depending on an enhanced AF signal intensity from increased elastosis and a reduced SHG signal originating from a decreasing amount of collagen fibers [14,16,21,24,30,31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…The gray-level co-occurrence matrix (GLCM) evaluates visual texture of the image based on pixel intensity spatial arrangement statistics (Haralick et al, 1973), and is reportedly the most common and sensitive texture descriptor (Adur et al, 2014). The gray-level co-occurrence matrix (GLCM) evaluates visual texture of the image based on pixel intensity spatial arrangement statistics (Haralick et al, 1973), and is reportedly the most common and sensitive texture descriptor (Adur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%